Treatment of Congenital Radioulnar Synostosis Using a Free Vascularized Fascia Lata Graft. Issue 6 (7th May 2022) - Bai, Fan; Chen, Shanlin; Liu, Lu; Tong, Dedi; Li, Pengcheng; Rong, Yanbo; Wu, Jingheng; Liu, Bo; Yang, Yong; Wang, Shufeng
Abstract: Objective: To describe the modified mobilization surgery technique that uses a free vascularized fascia lata graft as the interposition graft, and to evaluate the outcome of this procedure in treating congenital radioulnar synostosis (CRUS). Methods: Eleven patients (eight boys and three girls with an average age of 6.0 years) were treated using this procedure between 2012 and 2017 in our institution. Five bilateral cases (four left forearms and one right forearm were treated), and six unilateral cases (three left forearms and three right forearms) were included. All 11 cases were treated with mobilization procedure with free vascularized fascia lata as the interposition graft, and were followed‐up for an average of 2.2 years (range, 2–4 years). The parental satisfaction, postoperative ankylosis at proximal radioulnar joint, and active range of forearm rotation motion (measured by physical examination) were evaluated at the last follow‐up. Results: The average preoperative fixed pronation angle was 67.3° (range, 20°–90°). Ipsilateral thumb hypoplasia was noted in one case, and cleft palate and bilateral thumb hypoplasia were noted in one case; none of the patients had a family history of congenital radioulnar synostosis. Pronation and supination splints were used 3 days after the operation and were worn every night for 4–6 months postoperatively. Active and passive rehabilitation for elbow flexion and forearm rotation was initiated 4 weeks postoperatively. All patients were followed up for at least 2 years (average, 26 months; range, 24–48 months). The average forearm pronation range was 39° (range, 20°–60°), and the average forearm supination range was 33.2° (range, 10°–60°) at the latest follow‐up. Re‐ankylosis occurred in one case. An osseous bridge developed between the radius and ulna at the osteotomy site in one case. Radial nerve paralysis developed in two cases and spontaneously resolved 2 months later. Plate breakage was noted in one case 9 weeks postoperatively; however, union was achieved 7 months later. Conclusion: Mobilization of proximal radioulnar synostosis using a free vascularized fascia lata graft as the interposition graft may prevent re‐ankylosis and restore the forearm rotation function, making it a good option for the surgical treatment of CRUS. Abstract : Fascia lata can be used as interposition in mobilization procedure to avoid postoperative re‐ankylosis in congenital radioulnar synostosis patients, we tried this novel technique in 11 children in our clinic from 2012 to 2017, the parental satisfaction, radiological findings, and active forearm rotation function were satisfying after 2 years follow‐up.